THE ANTI-MELANOMA ACTIVITY OF THE HISTONE DEACETYLASE INHIBITOR PANOBINOSTAT (LBH589) IS MEDIATED BY DIRECT TUMOR CYTOTOXICITY AND INCREASED TUMOR IMMUNOGENICITY - Woods, David M. (2013)
OBJECTIVES: Melanoma is the deadliest skin cancer, and its incidence has been increasing faster than any other cancer. Although immunogenic, melanoma is not effectively cleared by host immunity. In this study, we investigate the therapeutic, anti-melanoma potential of the histone deacetylase inhibitor (HDACi) Panobinostat (LBH589) by assessing both its cytotoxic effects on melanoma cells as well as enhancement of immune recognition of melanoma. METHODS: Utilizing murine and human melanoma cell lines, we analyze the effects of LBH589 on proliferation and survival. Additionally, we analyze expression of several immunologically relevant surface markers and melanoma differentiation antigens, and the ability of LBH589 treated melanoma to activate antigen specific T-cells. Finally, we assess the in vivo effects LBH589 in a mouse melanoma model. RESULTS: Low nanomolar concentrations of LBH589 inhibit the growth of all melanoma cell lines tested, but not normal melanocytes. This inhibition is characterized by increased apoptosis as well as a G1 cell cycle arrest. In addition, LBH589 augments the expression of MHC and co-stimulatory molecules on melanoma cells leading to an increased ability to activate antigen specific T-cells. Treatment also increases expression of melanoma differentiation antigens. In vivo, LBH589 treatment of melanoma-bearing mice results in a significant increase in survival. However, in immunodeficient mice, the therapeutic effect of LBH589 is lost. CONCLUSIONS: Taken together, LBH589 exerts a dual effect upon melanoma cells by affecting not only growth/survival but also by increasing melanoma immunogenicity. These effects provide the framework for future evaluation of this HDAC inhibitor in melanoma treatment.